The origin of proton mass from J/$${Ψ }$$ Ψ photo-production data - Rong Wang; Xurong Chen; Jarah Evslin (European Physical Journal C: Particles and Fields, 2020)
Abstract The trace of the stress tensor characterizes the transformation of a theory under rescaling. In quantum chromodynamics (QCD), this trace contains contributions from the bare masses of the quarks and also from a purely quantum effect, called the QCD trace anomaly. It affects all masses in the theory. We present an estimation of the QCD trace anomaly from the near-threshold $$\hbox {J}/{Ψ }$$ J/Ψ photo-production data of the GlueX experiment, at JLab. We apply a vector meson dominance model to describe the photo-production of $$\hbox {J}/{Ψ }$$ J/Ψ and a running strong coupling which includes the nonperturbative effects in the low $$μ ^2$$ μ2 region. Despite the large uncertainty, we find that the experimental data favors a small value of the trace anomaly parameter $$b=0.07± 0.17$$ b=0.07±0.17 . We report the resulting proton mass decompositions at $$μ ^2=0.41\hbox { GeV}^2$$ μ2=0.41GeV2 and $$μ ^2=4\hbox { GeV}^2$$ μ2=4GeV2 .